The Effect of Motor Activity Based Learning on the Acquisition of Two Tennis Groundstroke Skills - Abbas , Abbas Fadhel (Journal of Physical Education, 2025)
This research is concerned with the effect of learning on movement activity to develop groundstroke (Forehand and backhand) tennis skills for 14 year age group female players at Diyala specialized Center of Baghdad. The study was conducted with two groups (experimental and control), one of which was taught using motor activity based instructional modules, while the other was taught through traditional teaching techniques. Analysis included before and after for each set of skills. The results showed that the experimental group was able to achieve a significantly better improvement in accuracy and consistency than the control group, thanks to variety of practice including immersion in practical experience. This made them even more motivated to learn the strokes and deepened their understanding of what is the base technical element of each smash and clear. Conversely, the control group was able to reduce EF through mere repetition. The findings of the study provide support for programs with structured progressive educational content that mesh practical and sensory-motor learning experience, expedite skill acquisition as well as maintain performance progression in young tennis players.